Criminology - Boldbaatar, Jigjidsurengiin, 1960-; Bayarmagnai, R.; Dashdavaa, Z.; Khaltar, T.; Anudari, O. (Odyn), editor; Munkhdorj, B. editor; Orkhon Ikh Surguulʹ (Ulaanbaatar Published by "Free Press Foundation" NGO, 2024)
Presented to the public, this work endeavors to reinterpret traditional concepts of criminological theory within a new historical context.
At head of title: Orkhon University.
Includes bibliographical references (pages 133-135).
Keywords: Criminology